Estudo da interação entre polímeros biodegradáveis e polianilina para o desenvolvimento de embalagens condutoras e inteligentes - Oliveira, Ana Carolina Salgado de (2018)
In this study, blends were developed from biodegradable polymers and polyaniline (PANI) in order to obtain conductive and smart packaging with possible application in the food segment. The blends were characterized according to morphological (optical microscopy and SEM), structural (FTIR, RAMAN), thermal (TGA) and electrical (Hall effect) properties. The main polymers used in the blends were based on two biodegradable polymers: whey protein isolate (WPI) and chitosan. First, PANI was synthesized in its conductive form b y doping it with dodecylbenzene sulphonic acid and it was characterized according to structural (FTIR, RAMAN), Thermal (TGA) and electrical (Hall effect) properties. Based on the Hall effect analyses, PANI presented high conductive values and positive charge carriers, showing the efficiency of the proposed synthesis. After that, blends of WPI and different concentrations of PANI (20, 40, 60, 80 e 100 mg/mL) were synthesized. These blends presented immiscible and low conductivity (10 -3 S/cm). The chitosan and PANI blends were synthesized using four different formulations: chitosan and PANI (i); chitosan, PANI and glutaraldehyde (ii); chitosan, PANI and glycerol (iii); and, chitosan, PANI, glutaraldehyde and glycerol (iv). Firstly, formulation i and ii were synthesized with factorial design with 3 replications and differents concentrations: 20, 40, 60, 80 e 100 mg/mL of PANI, 2% of chitosan dissolved into 2% acetic acid water solution and 0 mL ou 6,25 x 10 -³ μL of glutaraldehyde. Among these formulations, all presented negative charge carriers and higher conductivity values were observed for PANI concentration of 80 mg/mL and 100 mg/mL, presenting 10 -1 S/cm value and 10 -2 S/cm without and with glutaraldehyde, respectively. When formulation iii and iv were synthesized using completely randomized design with 3 replications and differents concentrations: 80 mg/mL and 100 mg/mL of PANI, 1% and 2% of chitosan dissolved into 2% acetic acid water solution; 10%, 20%, 30 % of glycerol and 0 mL ou 6,25 x 10-³ μL of glutaraldehyde. In this new group of formulations the charge carriers were negative. When morphological and electrical properties were analyzed together, the best results were obtained with 2% of chitosan and 80 or 100 mg/mL of PANI reaching conductivity values of 10 -1 S/cm. However, between the iii and iv formulation the glutaraldehyde was not efficient in its cross-linked action, as a reduction in the thickness of the films was not observed, what happened for formulations i and ii. The glycerol was efficient to increase chitosan/PANI blend conductivity. The association glycerol-glutaraldehyde was the most efficient to increase the blends conductivity because the increase reached 789% when it was compared 2% chitosan, 100 mg/mL of PANI and glutaraldehyde blend with and without glycerol; and a 239,8% increase when 2% chitosan, 100 mg/mL of PANI blend was compared to 2% chitosan, 100 mg/mL of PANI and 30% of glycerol.